Dikotomi Bebas Nilai dan Nilai Pendidikan dalam Pembelajaran Sejarah - Yudi Setianto (Jurnal Pendidikan dan Kebudayaan, 2012)
The aim of writing this article is to offer a win-win solution to put history learning, both as a pure social science as well as an education and learning tools for students. This study used qualitative descriptive approach. As a science, history should be objective and at the same time keep the value-free concept. In the context of history, objectivity means truth and honesty, that is all facts must be disclosed transparantly. However, in history learning, not all the historical facts should be revealed fully. Yet, it does not necessarily mean that history learning is not objective or even denying the facts. For the wiser purpose, the history polarisation aiming at growing students’ nationalisme, patriotism, and other noble educational objectives, it is not possible to treat history as a tool to legitimate social conflicts or even the nation disintegration. History in learning should keep objective in uncovering historical facts, while also maintain the purpose of the learning itself. History as a learning must be built upon the foundation and aim of the national education system. Thus, history as a school subject having particular education objectives must be put in line, side by side, compromise with its position as a social science, without eliminating the principles of one or both of them. History learning uses filtered historic facts, so the learners are led to be wise people. ABSTRAK Tujuan penulisan artikel ini untuk menemukan win-win solution, dalam rangka memisahkan sekaligus saling menghormati antara Sejarah dalam ranah ilmu murni dan Sejarah dalam domain pendidikan atau pembelajaran ke siswa. Penulisan ini menggunakan pendekatan kualitatif deskriptif. Sejarah sebagai ilmu dituntut objektif, dan tetap menjaga kebebasan nilai (value-free). Dalam konteks Sejarah, objektivitas bisa diterjemahkan sebagai kebenaran dan kejujuran, fakta yang direkonstruksi dituntut dikemukakan secara transparan. Namun, dalam ranah pembelajaran Sejarah, Sejarah tidak mungkin dikemukakan secara objektif. Hal ini bukan berarti jika pembelajaran bersifat subyektif ataupun mengingkari fakta. Bagi tujuan yang lebih bijaksana, polarisasi Sejarah, yaitu dalam rangka menumbuhkan nasionalisme, patriotisme serta tujuan-tujuan pendidikan lainnya, tidak mungkin disandingkan dengan sejarah sebagai alat legitimasi konflik sosial, bahkan disintegrasi bangsa. Ilmu Sejarah tetap bersifat objektif dalam mengungkap fakta Sejarah, sementara itu tujuan pelajaran Sejarah merupakan bagian dari tujuan pendidikan. Sejarah sebagai bahan pelajaran harus disusun searah dengan dasar dan tujuan Pendidikan Nasional. Sejarah sebagai mata pelajaran yang mempunyai misi tertentu dan Sejarah sebagai ilmu, harus dipadukan dalam konsep yang jelas tanpa mengorbankan prinsip-prinsip salah satunya atau keduanya. Pembelajaran Sejarah menempatkan fakta-fakta Sejarah yang disaring, demi tujuan pendidikan agar Sejarah menjadikan yang mempelajarinya lebih bijaksana.